Fuzzy Inferensi System dengan Tsukamoto pada Penilaian Kepuasan Pelangan di Cafe Pasco Pematangsiantar - Dolli Sari Sinaga; Feby Widya Sari (LPPM STIKOM Tunas Bangsa, 2019)
The development of cafe business is increasingly rapid, demanding that the cafe always create innovations and new concepts that are able to attract more consumers. The main key in attracting consumers in addition to innovation and new concepts is the ability of cafes to provide satisfaction to consumers. The purpose of this research is to find out whether customers are satisfied with the service at Pasco Cafe. The method used in this study is the Fuzzy Tsukamoto method. Data was collected by distributing questionnaires / questionnaires to 150 customers at Cafe Pasco. The variables used to assess satisfaction given by the Cafe to consumers are infrastructure (X), price (Z) and service (Z). Where infrastructure has criteria (complete and incomplete [1; 9]), prices have criteria (cheap, normal and expensive [1; 6; 9]) and services have criteria (satisfied and dissatisfied [2; 9]. example of infrastructure cases has a value of 6 and the price has a value of 5. The results of the assessment of customer satisfaction with service in the Cafe Pasco category satisfied with a value of 5.2462